Firm recruitment behaviour: sequential or non-sequential search? - Jos van Ommeren; Giovanni Russo (Institute for the Study of Labor (IZA), 2009)
In the extensive job search literature, studies assume either sequential or non-sequential search. Which assumption is more reasonable? This paper introduces a novel method to test the hypothesis that firms search sequentially based on the relationship between the number of (rejected) job applicants and the number of employees hired. We use data compiled from filled vacancies for the Netherlands. Different types of search methods are distinguished. Our results imply that when firms use advertising, private or public employment agencies, which together cover about 45 percent of filled vacancies, sequential search is rejected. For about 55 percent of filled vacancies however, sequential search cannot be rejected. In line with theoretical considerations, when firms use search methods that rely on social networks, sequential search cannot be rejected.
urn:nbn:de:101:1-20090304406
Keywords: J63; 330; Sequential search; recruitment; Personalbeschaffung; Arbeitsnachfrage; Arbeitsuche; Offene Stellen; Niederlande